2014
DOI: 10.14321/qed.1.2.0038
|View full text |Cite
|
Sign up to set email alerts
|

Transgender Worldmaking in Cyberspace: Historical Activism on the Internet

Abstract: Advances in digital technology have provided new opportunities for historical activism, particularly through the collaborative channels of cyberspace. This article examines transgender historical activism on the Internet by identifying three types of worldmaking projects that respond to nonexistent or impoverished historical record keeping. With the affordances of cyberspace, transgender worldmaking invites collaborative, innovative, experimental, and politically charged historical projects that enact alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The articles describe trans individuals sharing identity/expression options with others, with studies finding that trans individuals often learned about the concept of transness from other trans individuals (Kosenko et al, 2018;Saltzburg & Davis, 2010). Studies also found that trans individuals who are physically transitioning may share detailed information about the impact of HRT over time through videos and photos (Eckstein, 2018;Hawkins & Gieseking, 2017;Miller, 2017;Rawson, 2014). Information regarding non-medical transition was also shared, such as beauty/make-up tips, tips on how to "pass", suggestions for developing "masculine mannerisms", along with other appearance-related information (Cannon, 2017;Gauthier & Chaudoir, 2004;Miller, 2017).…”
Section: Identity and Expressionmentioning
confidence: 99%
“…The articles describe trans individuals sharing identity/expression options with others, with studies finding that trans individuals often learned about the concept of transness from other trans individuals (Kosenko et al, 2018;Saltzburg & Davis, 2010). Studies also found that trans individuals who are physically transitioning may share detailed information about the impact of HRT over time through videos and photos (Eckstein, 2018;Hawkins & Gieseking, 2017;Miller, 2017;Rawson, 2014). Information regarding non-medical transition was also shared, such as beauty/make-up tips, tips on how to "pass", suggestions for developing "masculine mannerisms", along with other appearance-related information (Cannon, 2017;Gauthier & Chaudoir, 2004;Miller, 2017).…”
Section: Identity and Expressionmentioning
confidence: 99%
“…As demonstrated in other PAR studies with marginalized communities in Canada (e.g. Ginn and Kulig, 2015; Riecken et al., 2006; Sakamoto et al., 2009), PAR researchers view marginalized people not only as research participants but as individuals who hold important knowledge and skills that offer innovative solutions to the problems they face.…”
Section: Literature Reviewmentioning
confidence: 89%
“…Cavalcante (2016) has similarly found that transgender-centered websites enable “architectures of organized care and concern” as members of trans counterpublics readily support one another through physical transition in an interactive media environment made possible through new media outlets. Rawson (2014) compellingly argues that transgender worldmaking online is an especially important site of historical activism because, “cyberspace provides a revolutionary tool for creating, sharing, and preserving trans histories that would otherwise remain untold.” Barnett (2015) has detailed how blogs authored by trans people have created a “transsexual counterpublic” in which the human body is constructed as a natural and continual site of transformation in opposition to dominant constructions of the body and gender as normatively immutable.…”
Section: Trans Women Media and Representationmentioning
confidence: 99%